Urban carbon governance and the transition toward low-carbon urbanism: review of a global phenomenon. Issue 3 (4th May 2014) - Lo, Kevin
Abstract : This paper reviews the literature on urban carbon governance, which has become a burgeoning area of research. Since the early 1990s, the field has grown and diversified geographically, theoretically and methodologically, and now encompasses a wide range of topics, including governing techniques, limitations and challenges, central-local relations, municipal networks, network governance and grassroots initiatives. Given the increasingly global nature of low-carbon urbanism and governance, these studies have expanded our knowledge on the complexity and plurality of the role of cities in addressing climate change. This review serves as a consolidated guide for researchers, policymakers and students in this field.